Penguatan Nilai Toleransi Melalui Pendidikan Multikultural pada Pembelajaran Sejarah Jenjang SMA - Santosa, Yusuf Budi Prasetya; Maulana, Wildhan; Djono, Djono (Jurnal Artefak, 2025)
The degradation of the value of tolerance that occurs today as a result of the strengthening of social hegemony, class sentiment, and primordialism requires anticipatory efforts, one of which is by strengthening the value of tolerance through the means of learning history at school. The research aims to analyze the strengthening of tolerance values via multicultural education content in high school history learning. By using a qualitative method through a literature study approach, trying to analyze various relevant literature and documents related to the theme of the study. Data analysis techniques using content analysis, data validity using a triangulation model by checking findings and comparing between sources. The research findings include a description of the content of tolerance values and the design of strengthening these values through multicultural education in high school history learning. The results show that strengthening the value of tolerance through multicultural education in high school history learning can be integrated with an additive approach, namely by presenting factual issues around intolerance, and encouraging students to actualize the value of tolerance extracted from previous history material to address factual issues or applied in the context of social studies-based history learning. This research contributes to history teachers and is used as a reference to optimize history learning as an alternative means of strengthening students' tolerance values.